Design, Synthesis and Biological Evaluation of Xanthone Derivatives for Possible Treatment of Alzheimer's Disease Based on Multi‐Target Strategy. Issue 10 (21st September 2020) - Yang, Aihong; Yu, Qiao; Ju, Hui; Song, Lulu; Kou, Xiaodi; Shen, Rui
Abstract: Four xanthone derivatives were synthesized and evaluated as acetylcholinesterase inhibitors (AChEIs) with metal chelating ability and antioxidant ability against Alzheimer's disease (AD). Most of them exhibited potential acetylcholinesterase (AChE), butylcholinesterase (BuChE) inhibitory, antioxidant and metal chelating properties. Among them, 1‐hydroxy‐3‐[2‐(pyrrolidin‐1‐yl)ethoxy]‐9 H ‐xanthen‐9‐one had the highest ability to inhibit AChE and displayed high selectivity towards AChE (IC50 =2.403±0.002 μM for AChE and IC50 =31.221±0.002 μM for BuChE), and it was also a good antioxidant (IC50 =2.662±0.003 μM). Enzyme kinetic studies showed that this compound was a mixed‐type inhibitor, which could interact simultaneously with the catalytic anionic site (CAS) and the peripheral anionic site (PAS) of AChE. Interestingly, its copper complex showed more significant inhibitory activity for AChE (IC50 =0.934±0.002 μM) and antioxidant activity (IC50 =1.064±0.003 μM). Molecular dockings were carried out for the four xanthone derivatives in order to further investigate the binding modes. Finally, the blood‐brain barrier (BBB) penetration prediction indicated that all compounds might penetrate BBB. These results suggested that 1‐hydroxy‐3‐[2‐(pyrrolidin‐1‐yl)ethoxy]‐9 H ‐xanthen‐9‐one was promising AChEI with metal chelating ability and antioxidant ability for the further investigation. Abstract :